PKM ibu rumah tangga dan kelompok wanita tani Desa Pancana - Nahriana Nahriana; Ernawati S. Kaseng; Taty Sulastry (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Pancana Village is one of the villages in the district of Tanete Rilau, Barru District which is one of the areas in South Sulawesi that has the potential sea resources in the form of sea of snapper, fish, mackerel, tuna, and fish Other commercial that is so large in number, and very possible for the development of marine fish industry centers and also diversified processed from this sea fish into food such as brain-brain fish, fish balls, fish and fish pepes, shrimp, crabs King and sea shells etc. Currently, the management of seafood such as pepes, shrimp mango sauce, grilled squid and various sea shells is still very less done at the inhabitants of Pancana village. People in Pancana village especially processing on farmers or fishermen fish, shrimp, crabs etc, only sell directly the catch or only on the group of partners, generally still traditionally managed and rely solely on cultivation Only sold directly, so the new product is limited to marine fish sold raw or dry sold at a very cheap price. The most basic problem is related to the lack of knowledge and skills of craftsmen or sea fish fishermen farmers or other sea products in groups of partners about the quality of marine fish and sea prawns and diversification of processed results Sea fish, shrimp, clams and crabs that can motivate fishermen farmers to develop processed products with fish-based, shrimp, squid, crab etc. into the processed diversification and cultivation of seafood, and packaging is still simple. Therefore, the purpose of community dedication activities through the Community Partnership Program (PKM), as follows: 1) improvement of seaweed cultivation process, 2) diversification of processed seaweed cottonii sp, and 3) packaging and labeling process. The method of implementing community service activities through Community Partnership Program (PKM), through socialization and training and with mentoring on the production process and the packaging process, so that the activities are expected In this program, can lead to the enhancement and mastery of the knowledge and skills of craftsmen and cultivters on the KUB and farmer Group; Fisherman fish or other seafood group of partners so that later can run continuously and can increase the economy of farmers and fishermen of sea fish and shrimp, as well as crabs and their families.